2017
DOI: 10.1093/jac/dkx048
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing frequency amongst patients in primary care: a cohort study using electronic health records

Abstract: Background: Reducing inappropriate antibiotic prescribing in primary care is a public health priority. Objectives: We hypothesized that a subset of patients account for the majority of antibiotic prescriptions in primary care. We investigated the relationship between the total amount of antibiotics prescribed, individual-level antibiotic use and comorbidity. Methods: This was a cohort study using electronic health records from 1 948 390 adults registered with 385 primary care practices in the UK in 2011–13. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 27 publications
6
63
0
3
Order By: Relevance
“…20 In the United Kingdom, 30% of patients are prescribed at least one antibiotic annually. 21 Our findings support the hypothesis that antibiotics may be contributing to the increasing prevalence and earlier age at onset of nephrolithiasis. 22 Given that children receive more antibiotics than any other age group, and 30% of antibiotics prescribed during ambulatory care visits are inappropriate, 23-25 these findings provide another reason to reduce inappropriate outpatient antibiotic use.…”
Section: Discussionsupporting
confidence: 86%
“…20 In the United Kingdom, 30% of patients are prescribed at least one antibiotic annually. 21 Our findings support the hypothesis that antibiotics may be contributing to the increasing prevalence and earlier age at onset of nephrolithiasis. 22 Given that children receive more antibiotics than any other age group, and 30% of antibiotics prescribed during ambulatory care visits are inappropriate, 23-25 these findings provide another reason to reduce inappropriate outpatient antibiotic use.…”
Section: Discussionsupporting
confidence: 86%
“…The differences could be because of different patient populations. [15][16][17] The analysis of indications for the admissions in MICU in this study showed that the most common disease for which patients were admitted in intensive care units included organophosphorus poisoning (24.86%), snake bite (15.14%), bilateral pneumonitis (12.71%), HELLP syndrome (12.14%), respectively and the least common pathologies included COPD with respiratory failure (10.43%), meningitis (6.14%), sepsis with MODS (4.71%), GBS (3.86%), lung abscess (3.0%), alcoholic liver disease (1.57%), chronic kidney disease (1.43%), encephalitis (1.14%), infective endocarditis (1.57%) and stroke (1.29%). In contrast, the most common indications for admission in MICU in study conducted by Crucio D was nosocomial pneumonia (21%), community pneumonia (14%), intra-abdominal infections (12%), genitourinary infections (12%), CNS infections (6.7%), skin infection (6.7%), sepsis (6.7%), etc.…”
Section: Discussionmentioning
confidence: 99%
“…11 Thirty percent of patients are prescribed at least 1 antibiotic annually. 12 In this issue of AJKD, Ferraro et al 13 reported that prior antibiotic exposure is associated with incident symptomatic kidney stones among women in the well-characterized Nurses' Health Study (NHS) I and II cohorts. Strengths of the study include prospectively collected antibiotic exposures and, for a subset of participants, availability of 24-hour urine chemistry test results.…”
mentioning
confidence: 99%